2008
DOI: 10.4296/cwrj3302125
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Uncertainty in Canadian Low Flow Hydrometric Data

Abstract: The uncertainty of estimated daily mean discharge is 5% at the 95% confidence interval (Herschy, 1999a). The use of this unique value requires acceptance of the assumption of uniformity of uncertainty within the hydrometric dataset. It is the implicit responsibility of each researcher to challenge this assumption with respect to any given hypothesis test. This paper evaluates this assumption of uniformity for a subset of the hydrometric dataset-low flow in Canada. Studies of low flow phenomena are becoming mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 16 publications
(15 reference statements)
1
19
0
Order By: Relevance
“…streamflow gauging and stage–discharge relationship uncertainties) will lead to a certain degree of deviations between the observed and simulated results. In particular, the ability to obtain reliable low‐flow measurements is complicated by factors such as hyporheic flow exchange and the presence of river ice and aquatic vegetation (Hamilton, ), leading to considerable uncertainties in the measured discharge. The fact that over 35% of the observed data used are obtained under ice conditions (Water Survey of Canada, hydrometric data: http://www.wsc.ec.gc.ca/applications/H2O/index-eng.cfm) implies considerable uncertainty in the measured low‐flow values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…streamflow gauging and stage–discharge relationship uncertainties) will lead to a certain degree of deviations between the observed and simulated results. In particular, the ability to obtain reliable low‐flow measurements is complicated by factors such as hyporheic flow exchange and the presence of river ice and aquatic vegetation (Hamilton, ), leading to considerable uncertainties in the measured discharge. The fact that over 35% of the observed data used are obtained under ice conditions (Water Survey of Canada, hydrometric data: http://www.wsc.ec.gc.ca/applications/H2O/index-eng.cfm) implies considerable uncertainty in the measured low‐flow values.…”
Section: Resultsmentioning
confidence: 99%
“…errors in precipitation measurement, and interpolation uncertainties due to elevation and orographic effects; (ii) output uncertainty, e.g. errors in observed discharge data due to hydrometric data uncertainties (Pelletier, ; Hamilton, ; Hamilton and Moore, ) and stage–discharge relationship uncertainties (Shrestha et al ., ); (iii) structural uncertainty, arising from simplified and/or incomplete representation of hydrologic processes in the model; and (iv) parameter uncertainty, arising from the need to calibrate parameter values based on observed streamflow. Difficulties in reproducing some of the hydrologic indicators using the goodness‐of‐fit (GOF) measures [coefficient of determination, R 2 , and Nash–Sutcliffe coefficient of efficiency (NSE)] (Nash and Sutcliffe, ) have been documented by previous studies, such as simultaneous representation of low flow and high flow with a single set of parameter values (Wagener, ; Fenicia et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the SWAT model calibration may also be affected by a number of other factors, such as river-ice, which can affect the quality of discharge records, especially during break-up (e.g., Pelletier, 1990;Hamilton, 2008). These discharge uncertainties influence the model calibration and validation results.…”
Section: Swat Calibration Resultsmentioning
confidence: 99%
“…In fact, once an ice‐cover forms or during dynamic ice events, the usefulness of water level monitoring for estimating Q remains questionable. Detailed analyses of Canadian Q data suggested that the uncertainty in Q values under various situations particularly in the north could well exceed the theoretical uncertainty that is generally assumed for the typical global hydrometric data set, but remains to be quantified [ Hamilton , ; Hamilton and Moore , ].…”
Section: Discussionmentioning
confidence: 99%